Solution:
1. Distribute the constants inside the parentheses:
-11(p+5) and 5(p-5)
- -11(p+5) = -11p - 55
- 5(p-5) = 5p - 25
2. Rewrite the equation:
-11p - 55 + 5p - 25 = -5p - p - 80
3. Combine like terms:
- On the left side: -11p + 5p - 55 - 25 = -6p - 80
- On the right side: -5p - p - 80 = -6p - 80
4. The equation is now:
-6p - 80 = -6p - 80
5. Add 6p and 80 to both sides:
-6p - 80 + 6p + 80 = -6p - 80 + 6p + 80
6. Simplify both sides:
0 = 0
Since both sides of the equation are identical, this means the equation is true for all values of p.